Penerapan Model Pembelajaran ROPES untuk Meningkatkan Minat dan Hasil Belajar IPA Siswa Kelas IV SDN 01 Karangasem - Fatkha Khasanah (Perkumpulan Kualitama Edukatika Indonesia, 2021)
The problem in this study is whether the application of the ROPES learning model can increase the interest and learning outcomes of students at SDN 01 Karangasem, Talun, Pekalongan Regency?. The research was carried out in 2 cycles, each cycle consisting of 4 stages, namely planning, implementing actions, observing and reflecting. From the results of the study showed an increase in learning outcomes and student interest in learning. Based on the results of the reflection in the first cycle, the results obtained include: the average percentage of student activity is 63.2%, the results of the first cycle evaluation with the percentage of classical learning completeness are 68.75% and student interest in the application of the ROPES model gets an average of 68%. While the results of reflection in the second cycle have increased, namely: the average percentage of student activity is 77.2%, the results of the second cycle evaluation with the percentage of classical learning completeness are 87.5% and student interest in learning after the application of the ROPES model gets an average of 82%. Thus it can be concluded that by applying the ROPES learning model can increase interest in learning because students are interested in learning and students do not feel bored or bored with mathematics lessons.